Principles for Progress : Essays on Religion and Modernity by `Abdu'l-Bahá. - McGlinn, Sen. (Leiden : Leiden University Press, 2018)
This book presents three of the works of Abduʼl-Bahā, son of the founder of the Bahāʼi Faith, dealing with social and political issues. In The Secret of Divine Civilization (1875) Abduʼl-Bahā supports the administrative and broader social reforms of Mirzā Hosayn Khān, but looks mainly for organic reform through the efforts of Iranian intellectuals to waken and educate the masses. In this work, Abduʼl-Bahā gives virtuous and progressive Islamic clerics a leading role among these intellectuals, indeed most of his appeals are directed specifically to them. A Traveller's Narrative (1889/90) is an.
‎Translator's Notes to Selections from A Traveller's Narrative‎The Art of Governance; ‎Translator's Notes to The Art of Governance; ‎Further reading; ‎References; ‎Index
Print version record.
JSTOR
Keywords: Leadership -- Religious aspects; Political science -- Philosophy; Religion and state; Religion and politics; Babism; Civilization; Bahai Faith; Iran; Civilization; Leadership -- Aspect religieux; Religion et État.; Religion et politique; Babisme; Civilisation; Foi bahaïe.; civilization; Middle Eastern history; Islam; HISTORY / Middle East / Iran; Babism; Bahai Faith; Civilization; Leadership -- Religious aspects; Political science -- Philosophy; Religion and politics; Religion and state; Iran; Middle Eastern history; Islam; Electronic books